Writing skills improvement and development of critical thinking - S. Revutska (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article discusses the importance of improving writing skills along with the development of critical thinking. Despite significant achievements in this area, the study of critical thinking and its individual aspects as a complex phenomenon, as a necessary component of the process of improving writing skills, remains relevant. The interest in this topic will not diminish. The aim of the article is to substantiate the necessity of a comprehensive approach to writing skills improvement, that should be based on the simultaneous development of both writing skills and critical thinking skills for higher education students; to describe teaching techniques and technologies effective for the development of writing in a foreign language using critical thinking skills.